Respuestas
Respuesta dada por:
3
19. (ab + 5)(ab − 6)= a2b2 − ab − 30
20. (xy2 − 9)(xy2 + 12)= x2 y4 + 3xy2 − 108
21. (a2b2 − 1)(a2b2 + 7)= a4b4 + 6a2b2 − 7
Mas información en la imagen.
20. (xy2 − 9)(xy2 + 12)= x2 y4 + 3xy2 − 108
21. (a2b2 − 1)(a2b2 + 7)= a4b4 + 6a2b2 − 7
Mas información en la imagen.
Adjuntos:
![](https://es-static.z-dn.net/files/de0/d62ef194819f506e37d9957ed78dcdb0.png)
Preguntas similares
hace 7 años
hace 7 años
hace 7 años
hace 10 años
hace 10 años
hace 10 años
hace 10 años
hace 10 años